NARRATIVE DECORATIVE MOTIVES ON TORAJA TRADITIONAL CARVING - Sofyan Salam; Saleh Husain; Tangsi Tangsi; Jamilah Jamilah (JURNAL PAKARENA, 2022)
This study aims to explain the format and techniques of non-sacred narrative carving in Toraja. This research is classified as a qualitative research carried out in the field, namely in Tana Toraja and North Toraja. Data sources (1) artifacts in the form of non-decorative motifs of Toraja carving, both found in Toraja and elsewhere; (2) human data sources, namely Toraja sculptors and Toraja community leaders; and (3) documents that are documents containing descriptions, drawings or photographs of non-sacred decorative motifs of Toraja carving. Data collection techniques used were observation, interviews, and documentation. The collected data was analyzed with an interactive analysis model from Miles and Huberman. The results showed that: (1) The format of narrative carving art which is non-sacred in Toraja is (a) the format of a single scene narrative, (b) the panoramic narrative format, (c) the format of the narrative silmultanate. (2) The technique of depicting narrative carving art in Toraja, namely: (a) a realistic depiction technique, (b) the technique of presenting space there are two ways: presenting two-dimensional and three-dimensional space, and (c) the technique of composing elements (composition) which applied is symmetrical composition, asymmetric, rhythm, protrusion of object, and unity.